(untitled) (Modern education and development, 2025)
Цель данной статьи — рассмотреть влияние рекламы на проектную деятельность, а также её роль в достижении успешных результатов на всех этапах реализации проекта. В работе будет подробно анализироваться, как реклама способствует привлечению инвестиций, формированию позитивного имиджа проекта, коммуникации с целевой аудиторией и оптимальному использованию рекламных инструментов для достижения поставленных целей. The goal of this article is to examine the impact of advertising on project activities and its role in achieving successful outcomes at all stages of project implementation. The paper will analyze in detail how advertising contributes to attracting investments, forming a positive project image, communicating with the target audience, and the optimal use of advertising tools to achieve set goals.